Chaos in humanities and social sciences: An approach - Filipe, J. A.; Ferreira, M. A. M. (Proceedings of 12th Conference on Applied Mathematics, APLIMAT 2013, 2013)
Chaos theory has been first used in the applied and natural sciences and just then to the humanities and social sciences. Once introduced, chaos theory got rapidly a developing field. The idea of chaos has been then very significant both for empirical and for theoretical research not just in the applied and natural sciences but also in the humanities and social sciences. Being chaos extremely complex and difficult to be identified in the real world, even using the workable information, it is possible, anyway, up to a certain extent, to find specific mathematical relationships for problems to be solved. In this study some issues are presented in order to work this subject in the humanities and social sciences.